Evaluasi Kesesuaian Penggunaan Lahan Kota Jambi Tahun 2024 Terhadap Rencana Tata Ruang Wilayah Kota Jambi 2013-2033 - Dwi Marsiska Driptufany; Syaputra, Ilham; Fajrin Fajrin; Defwaldi Defwaldi; Dwi Arini (Politeknik Kampar, 2025)
Urban growth, both physical and non-physical, continues to increase, particularly in non-agricultural sectors such as settlements. Between 2000 and 2020, Jambi City experienced rapid and dense urban growth (Nugroho et al., 2022). Development must be carried out in accordance with the Regional Spatial Plan (RTRW) as stipulated in the Spatial Planning Law. This study aims to evaluate the current land use in Jambi City in 2024 to determine whether it aligns with the Jambi City RTRW for the period of 2013-2033. The method used in this research is overlay analysis, which involves combining attributes from the land use map and the spatial planning map of the RTRW. The results indicate that land use in Jambi City is predominantly residential (6,144.76 ha), followed by fields/cultivated land (5,468.64 ha), and shrubland (1,455.97 ha). The spatial utilization compatibility rate reaches 89.11%, demonstrating that the land use in Jambi City is in accordance with the established RTRW.